The association of insufficient gestational weight gain in women with gestational diabetes mellitus with adverse infant outcomes: A case-control study - Huang, Dabin; Liang, Mulin; Xu, Bin; Chen, Shan; Xiao, Yan; Liu, Hui; Yin, Dan; Yang, Jun; Wang, Ling; Pan, PianPian; Yang, Yihui; Zhou, Wei; et al. (Frontiers in Public Health, 2023)
Background: To investigate the association between insufficient maternal gestational weight gain (GWG) during dietary treatment, and neonatal complications of small-for-gestational-age (SGA) infants born to mothers with Gestational diabetes mellitus (GDM). Methods: A retrospective case-control study was conducted, involving 1651 infants born to mothers with GDM. The prevalence of a perinatal outcome and maternal GWG were compared among SGA, adequate- (AGA), and large-for-gestational-age (LGA); association with birth weight and GWG was identified using Pearson’s correlation analysis; binary logistic regression was performed to determine the odds ratio (OR) associated with SGA. Results: In total, 343 SGA, 1025 AGA, and 283 LGA infants met inclusion criteria. The frequency of SGA infants who were siblings (41.7% vs. 4.3% vs. 1.9%) and composite of complications (19.2% vs. 12.0% vs. 11.7%) were higher in SGA infants than in those in AGA or LGA infants group (both P < 0.01). GWG and pre-partum BMI were lower among the SGA mothers with GDM group (11.7 ± 4.5 kg, 25.2 ± 3.1kg/m2) than AGA (12.3 ± 4.6 kg, 26.3 ± 3.4 kg/m2) or LGA (14.0 ± 5.1 kg, 28.7 ± 3.9 kg/m2) mothers with GDM group. Binary logistic regression showed that siblings who were SGA (AOR 18.06, 95% CI [10.83-30.13]) and preeclampsia (AOR 3.12, 95% CI [1.34-7.30]) were associated with SGA, but not GWG below guidelines (P > 0.05). The risk of SGA (25.7% vs. 19.1% vs. 14.2%) and FGR (15.3% vs. 10.9% vs. 7.8%) was higher in GWG below guidelines group than those in GWG above and within guidelines group, the risk of low Apgar score (6.4% vs. 3.0% vs. 2.8%) was higher in GWG above guidelines group than that in GWG below and within guidelines group (P ＜0.05). Conclusion: Our findings demonstrated that GWG above and below guidelines, compared with GWG within guidelines, had a higher risk of adverse infant outcomes. Our findings also suggested that GWG below guidelines did not increase the risk for SGA, though SGA infants had more adverse outcomes among neonates born to mothers with GDM.